2018
DOI: 10.1101/349985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vascular defects ofDYRK1Aknockouts are ameliorated by modulating calcium signaling in zebrafish

Abstract: DYRK1A is a major causative gene in Down syndrome (DS). Reduced incidence of solid tumors and vascular anomalies in DS patients suggests a role of DYRK1A in angiogenesis, but in vivo evidence is lacking. Here, we used zebrafish dyrk1aa mutant embryos to understand DYRK1A function in the cerebral vasculature formation. Zebrafish dyrk1aa mutants exhibited cerebral hemorrhage and defects in angiogenesis of central arteries in the developing hindbrain. Such phenotypes were rescued by wild-type dyrk1aa mRNA, but no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…across multiple or all backgrounds analyzed here, modulated the expression of genes implicated in organic acid metabolism and pathogen defense. Indeed, similar GO terms, such as "metabolic process" and "immune system process" were also detected in published gene expression studies on the mbk-1 ortholog in other systems, including zebrafish embryos [41], and HeLa cells [42]. Collectively, these data provide evidence for mbk-1/DYRK1A playing an evolutionarily conserved role in these processes.…”
Section: Genes and Pathways Deregulated Upon Loss Of Mbk-1supporting
confidence: 70%
“…across multiple or all backgrounds analyzed here, modulated the expression of genes implicated in organic acid metabolism and pathogen defense. Indeed, similar GO terms, such as "metabolic process" and "immune system process" were also detected in published gene expression studies on the mbk-1 ortholog in other systems, including zebrafish embryos [41], and HeLa cells [42]. Collectively, these data provide evidence for mbk-1/DYRK1A playing an evolutionarily conserved role in these processes.…”
Section: Genes and Pathways Deregulated Upon Loss Of Mbk-1supporting
confidence: 70%
“…Interestingly, we found significantly decreased DYRK1A transcripts in calcium treated Tregs. A previous study also reported that vascular defects of DYRK1A knockouts are ameliorated by modulating calcium signalling in zebrafish [24], suggesting that DYRK1A can also serve as potential target for developing Treg based therapeutics of GV. To the best of our knowledge, we could not find any reports which suggests that calcium treatment can modulate GSK3B levels and activity and hence we assessed the effect of calcium treatment on GSK3B levels and activity.…”
Section: Discussionmentioning
confidence: 95%
“…Novel inhibitors presumably with higher specificity still needs particular careful investigation regarding both efficiency and toxicity. A recent report has shown the influence of DRK1A inhibition on vascular dysfunction in the context of developing cerebral vasculature via regulation of calcium signalling, using a zebrafish model [31]. In our previous report, a similar 3D sandwich model demonstrated its potential application in angiogenesis study [16].…”
Section: Discussionmentioning
confidence: 89%